(untitled) (Al-Academy, 2025)
Abstract The current research aimed to study and analyze the designs of medical beds used by the physically disabled (paralyzed of the lower limbs), to know and understand the extent to which these designs are suitable for the health condition of the disabled and to work on identifying the necessary design modifications to match the functional requirements of this segment. The research was limited to the designs of medical beds for the period (2023-2024) available in hospitals, specialized rehabilitation centers, and medical supply shops. Descriptive analysis was used, data collection, observation, sample surveying and then analyzing and interpreting data. The most important results were sample models recorded a clear functional weakness in terms of usability compared to the health condition of the disabled, lack of motor system in raising and lowering the bed led to the weakness of the current designs, which negatively affected the efficiency of use by the disabled.